DEVELOPMENT OF PD CONTROLLER FOR COMPARISON STABILITY STUDY IN MULTIPLE DIFFERENCE DISTURBANCES - Ab Ghani, Mohd Ruddin; Mohd Amin, Nur Huda; KASDIRIN , HYREIL ANUAR (2012)
This paper discusses the development of PD controller for comparison stability study in multiple difference disturbances. The multiple difference disturbances in this paper are added to the inverted pendulum model that based on robotic leg application such as pendubot. By applying the pendubot model via Simulink block diagram, the performance between the model and disturbances are compared for stability in the simulation results. The simulation results show that the PD controller play the main role to reduce or eliminate disturbances.